Profil Imunoglobulin-G Serum Kambing Peranakan Etawah Bunting yang Diberi Imbuhan Pakan Mineral Seng (SERUM IMUNOGLOBULIN-G LEVEL ON PREGNANT ETTAWAH CROSSBRED WERE GIVEN ZINC MINERAL) - Widhyari, Sus Derthi; Esfandiari, Anita; Sutama, I Ketut; Widodo, Setyo; Wibawan, I Wayan Teguh; Ramdhany, Rizal Rahadian (Jurnal Veteriner; Vol 18 No 1 (2017)DO - 10.19087/jveteriner.2017.18.1.24, 2017)
The objective of this study was to find out the effect of zinc supplementation on the profile of immunoglobulin-G (IgG) in the pregnant etawah-cross ewes. Fifteen etawah-cross ewes (3-6 years old and 30-50 kg body weight) were used in this experiment and they were divided into three groups each of which consisted of 5 ewes. The first group (Zn40) received 40 ppm Zn as control, the second group (Zn60) received 60 ppm Zn, and the third group (Zn80) received 80 ppm Zn. Blood samples were collected from jugular vein every two weeks, started at twelve weeks of pregnancy up to eight weeks post partum for immunoglobulin-G analysis. IgG level were analyzed by competitive Enzyme Linked Immunosorbent Assay (ELISA) technique. Results showed that there were no significant difference of immunoglobulin-G level (P>0,05) among the three treatment groups ( Zn40, Zn60, and Zn80). However, IgG level of Zn40 and Zn80 groups tended to decrease during the last staget of pregnancy until two weeks post partum. In conclusion, supplementation of 60 ppm Zn showed higher IgG level than Zn 80 ppm. ABSTRAK Penelitian ini bertujuan untuk mengetahui efek suplementasi seng (Zn) terhadap imunoglobulin-G (IgG) pada kambing peranakan etawah (PE) bunting. Penelitian ini menggunakan 15 ekor kambing PE umur sekitar tiga sampai enam tahun, bobot badan sekitar 30-50 kg dibagi ke dalam tiga kelompok, masing-masing terdiri dari lima ekor. Kelompok Zn40 (kontrol) diberi pakan mengandung mineral Zn 40 ppm, kelompok Zn60 mengandung mineral Zn 60 ppm, dan kelompok Zn80 mengandung mineral Zn 80 ppm. Sampel darah diambil melalui vena jugularis untuk menganalisis konsentrasi IgG. Pengambilan sampel darah dilakukan setiap dua minggu mulai umur kebuntingan 12 minggu sampai delapan minggu setelah melahirkan. Hasil penelitian menunjukkan bahwa konsentrasi IgG serum tidak menunjukkan perbedaan secara nyata antar kelompok (P>0,05) antara kelompok Zn 0, Zn 40 dan Zn 80 ppm. Kelompok Zn 40 ppm dan 80 ppm cendrung memperlihatkan konsentrasi IgG mengalami penurunan pada akhir kebuntingan sampai dua minggu setelah melahirkan. Pada kelompok Zn 60 ppm memperlihatkan konsentrasi IgG lebih tinggi dibanding kelompok Zn 80 ppm.
Keywords: etawah-cross goats,gravid, IgG, zinc